Pharmaceutical 3D Printing From Personalized Medicine to Super-Compounding Pharmacies: A Narrative Review - Michele Favia; Giulio De Vivo; Paola Cristina Cappelletto; Gabriele Bagaglini (Hospital Pharmacy, 2026)
Objectives: This narrative review explores how pharmaceutical 3-dimensional printing (3DP) can transform solid dosage form manufacturing from industrial mass production to truly personalized medicine, particularly for vulnerable cohorts such as pediatric, geriatric, and rare disease patients for whom conventional strengths and dosage forms are often inadequate and prompt unsafe manipulations like tablet splitting. It further aims to critically appraise the main 3DP technologies applicable in pharmacy – fused deposition modeling combined with hot melt extrusion, semi-solid extrusion, direct powder extrusion, selective laser sintering, and photopolymerization – in terms of active pharmaceutical ingredient stability, process and hardware complexity, and clinical scalability, within contemporary regulatory frameworks. Methods: A structured literature search of PubMed/MEDLINE up to April 2026, complemented by an analysis of European Medicines Agency (EMA) guidance documents, was performed to identify narrative and systematic reviews and case reports dealing with extemporaneous 3D-printed solid dosage forms in pharmacy settings, applying predefined inclusion criteria on study design, topic, publication date, and language. Results: The evidence converges on 5 key 3DP platforms currently suitable for pharmaceutical use, each enabling different strategies for dose titration, internal geometry design, and release modulation, while also presenting specific challenges related to thermal stress, material selection, and equipment requirements. Across these technologies, 3DP supports precise dosing, mini-tablet configurations, and personalized polypills that can enhance adherence and allow tailored pharmacokinetic profiles, and emerging hospital-based applications demonstrate the feasibility of point-of-care production supported by in-line, non-destructive quality control using process analytical technology tools such as NIR and Raman spectroscopy. Conclusion: Pharmaceutical 3D printing requires significant investment in infrastructure and navigating distinct regulatory paths, with the U.S. relying on 503A compounding guidelines while the EMA mandates strict EU GMP Annex 11 compliance for non-standard processes. The integration of non-destructive PAT tools, such as NIR and Raman spectroscopy, together with automated and validated digital systems, is essential for establishing an auditable framework for personalized, on-demand, hospital-based drug manufacturing.